Lemierre’s syndrome in a 16-year-old man associated with resolution of marked widespread ST elevation and a normal troponin level - Sylvia Amini; Salim Meghjee; Muhammad Rahim Khan (European Journal of Case Reports in Internal Medicine)
A 16-year-old man presented to the Accident and Emergence services with a 10-day history of shortness of breath, sore throat, vomiting, diarrhoea, poor oral intake, chest pain, jaundice, diplopia and reduced urine output. He was initially treated for sepsis, however, subsequent imaging and blood cultures confirmed the diagnosis of Lemierre’s syndrome (LS). LS, also known as necrobacillosis or post-pharyngitis anaerobic septicaemia is comprised of a triad of metastatic septic emboli secondary to pharyngitis, bacteraemia, and internal jugular vein thrombophlebitis. Fusobacterium necrophorum, a Gram-negative anaerobe, is the most common culprit of LS, followed by Fusobacterium nucleatum and anaerobic bacteria such as streptococci, staphylococci, and Klebsiella. LS is also called the forgotten syndrome because although use of antibiotics at first decreased the prevalence of LS, resistance to antibiotics has caused a rise in LS and it is no longer a forgotten disease. LS should be on the differential diagnosis of chest empyema if it follows pharyngitis or tonsillitis with neck pain, lymphadenopathy and sepsis, hence taking a thorough history is the key to diagnose it earlier. It is paramount to do chest X-ray, Doppler ultrasound of the neck veins and computed tomography (CT) scan of the neck and chest to look for features of LS. LS can be fatal if not diagnosed and treated properly. Empirical antibiotic therapy should be prescribed for a minimum of 3 weeks and should cover anaerobic bacteria and Gram-negative rods.